Budgetary dynamics of local governments in Paraná: Following incrementalism or punctuated balance? - Silva, Cristiane Aparecida da (2020)
This study aimed to analyze whether the budget process of Local Governments in Paraná follows the patterns of incremental change in budget allocations or occurrence of budget scores. Regarding the objectives, this study is characterized as descriptive. As for the approach, the research is characterized as qualitative. The sample corresponds to 39 local governments in Paraná, whose data collection concerns the time axis 2014 to 2017. The data were collected on the Brazilian Public Sector Accounting and Tax Information System (Siconfi) website in October 2018. Four were established analysis variables: education, health, public security and urbanism. Taking into account the analyzed aspects, it is concluded that the percentage variation in the budget appropriation data is distributed in a non-linear way, as illustrated by the graphic presentations and descriptive statistics, suggesting the occurrence of a punctuated equilibrium pattern and also the simultaneous scores in budget allocations between public policy sectors. The research limitations are related to the sample selection and analyzed variables. As notes for future research, it is suggested to use a larger longitudinal cut, as well as the application of models with statistical tests.